Pengaruh Etos Kerja Dan Efikasi Diri Terhadap Kinerja Aparatur Desa Pada Kecamatan Kewapante Kabupaten Sikka : Studi Kasus Pada Desa Ian Tena, Desa Wairkoja, Desa Seusina, Dan Desa Namangkewa - Yulistika Pricilia Nasa; Imanuel Wellem; Kristiana Reinildis Aek (Mutiara : Jurnal Penelitian dan Karya Ilmiah, 2023)
This research aimed to (1) determine the description of employee performance, work ethic, and self-efficiency; (2) snslyze the effect of work ethic and self-efficiencyon omployee performance either partially or simultaneously. The population in this research were village officials in the Kewapante Sub-district, Sikka regency (Ian Tena Village, Wairkoja village, Seusina Village, Seusina Village And Namangkewa Village) totaling 32 people. This research was carried out by means of a cencus or saturated sampling because the population was limited. Data were collected through quastionnaires and analyzed using descriptive methods and inferential statistics, namely multiple linear regression. Hypotesis testing is done through the F test and t-test. The results of the descriptive analysis showed that the variables of employee pervormance, work ethic, and self-efficacy were categorized as good. The t-test statistics showed that the work ethict and self-efficacy variables partially positively and significantly affected employee pervormance. The statistical results of the F test showed that work ethic and self-efficacy variables simultaneously significantly affected employe pervormance. The result of the determination analysis showed that the two independent variables in this research were able to explain the performance fluctuation of village officials in Kewapante Sub-district, Sikka Regency (Ian Tena Village, Wairkoja village, Seusina Village, Seusina Village And Namangkewa Village) of 58,1%.